A large-eddy simulation study on vortex-ring collisions upon round cylinders - New, Tze How (2022)
A large-eddy simulation based numerical study was conducted on head-on collisions between vortex-rings and round cylinders. The vortex-ring Reynolds number was Re = 4000, while the ratio of the cylinder diameter to vortex-ring diameter (i.e., diameter ratio, D/d) was varied from 4 to 1. Vortical behavior predicted by the present simulations is observed to agree well with an earlier experimental study [New, T. H., and Zang, B., “Head-on collisions of vortex rings upon round cylinders,” J. Fluid Mech. 833, 648 (2017)]. The present simulations also reveal additional flow details on the vortex dynamics and vortex-core trajectories, which have not been observed previously. First, vortex-dipoles produced by D/d ≤ 2 cylinders are cross sections of elliptic vortex-ringlets formed via vortex disconnection/reconnection of secondary vortex-ring segments. Second, the aspect ratio of the elliptic vortex-ringlets increases when a smaller diameter-ratio cylinder is used, and finally, they undergo axis-switching behavior. Furthermore, up to three sets of tertiary vortex-ring cores are formed along the D/d = 2 and 1 cylinder straight-edges where they subsequently merge with the secondary vortex-ring cores within the confines of the primary vortex-ring cores. This merged vortex core moves toward the collision axis and forms an inner vortex-dipole with a wall separated vortex. Along the convex surface, up to two sets of tertiary vortex-ring cores are observed for D/d = 2 and 1 cylinders, and trajectories of the vortex-dipoles agree well with the past experimental results. These observations support the notion that higher vortex-stretching levels resulting from the use of small diameter-ratio cylinders with higher surface curvatures underpin the wide range of vortical behavior observed here.